Medium-stress abrasive wear resistant plasma surfacing flux-cored wire and preparation method thereof
By adding vanadium elements to high-chromium cast iron to form a variety of carbides and using a welding wire formula with low-carbon cold-rolled steel strip outer skin, the problem of insufficient wear resistance and impact resistance of traditional welding wires under impact wear conditions is solved, and the problem of insufficient wear resistance and impact resistance of traditional welding wires is achieved. The material's high wear resistance and impact resistance improves, while simplifying the production process and reducing costs.
Patent Information
- Application Number
- CN202411464524.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2024-12-20
AI Technical Summary
Traditional wear-resistant materials are difficult to maintain high wear resistance and impact resistance at the same time under impact wear, and the existing welding wire formulas are complex and the production process is cumbersome, which limits the widespread application of materials.
Adding vanadium elements to high chromium cast iron substrates to form a variety of carbides, such as M7C3 and VC, and generating mesh and dispersed carbides through plasma surfacing process, improving the wear resistance and impact resistance of the material, and adopting low Carbon cold rolled steel strips serve as outer skins, simplifying processes and reducing costs.
It has achieved the improvement of high wear resistance and impact resistance of materials under plasma surfacing conditions, while simplifying the production process and reducing costs, which is suitable for the rapid development of modern industries.
Smart Images

Figure CN119159279A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of welding materials, and in particular relates to a medium-stress abrasive wear-resistant plasma surfacing flux-cored welding wire and a preparation method thereof. Background Art
[0002] Wear-resistant materials are widely used in mining, electric power, building materials, metallurgy, agricultural machinery and other industries. Traditional wear-resistant materials are difficult to meet the requirements of impact abrasive wear such as crushing, grinding, excavation and farming, because the brittleness of the material will increase accordingly when the hardness of the material is increased. How to make the material have both high wear resistance against wear and impact resistance is one of the key factors for the long service life of many key equipment.
[0003] The wear resistance of the surfacing alloy is mainly related to the hard phase in its microstructure, such as the shape and quantity of carbides, while the impact resistance is related to the matrix structure and the shape and size of carbides. The wear resistance of commonly used high-chromium cast iron mainly depends on the type, distribution and area ratio of carbides. The metallographic structure of high-chromium cast iron is generally primary carbide + austenite or martensite matrix. Martensite has high strength and hardness, but poor toughness. It is hard and brittle; austenite has good plasticity, low strength and certain toughness. M7C3 and M23C6 carbides are mainly formed in high-chromium cast iron. They are large in size, distributed in a network, have high hardness and high brittleness. Under impact wear conditions, the hard phase is easy to peel off in large quantities, which greatly reduces the wear resistance. When other carbide-forming elements such as W, Mo, Nb, V, etc. are added to high chromium cast iron, most of them will form fine and dispersed MC type carbides, especially VC, most of which are spherical and dispersed, and are not easy to fall off when impacted, thereby improving the impact wear resistance.
[0004] In the prior art, patent publication number CN111618474 A discloses an impact-resistant and wear-resistant self-shielded flux-cored welding wire, whose powder core contains ferrochromium, ferroboron, ferroniobium, ferromolybdenum, nickel powder and rare earth elements, etc., which mainly generate M7C3 type carbides, which are generally large in size and distributed in a network shape, and have limited impact resistance.
[0005] Patent publication number CN101406994 A discloses a high-carbon, high-chromium, high-niobium cast iron self-shielded flux-cored welding wire, the powder core of which contains ferrochrome, ferroniobium, tungsten, vanadium, etc. This formula adds a large amount of ferroniobium and a small amount of tungsten, vanadium, etc. to form MC-type carbides. The high price of ferroniobium limits the widespread use of this material. This formula has 14 to 18 kinds of powders, the formula is complex, the production process is cumbersome, and it is not conducive to large-scale production.
[0006] The purpose of the present invention is to provide a medium stress abrasive wear resistant plasma surfacing flux-cored welding wire and a preparation method thereof. By adding vanadium element on the basis of high chromium cast iron material, the wear resistance is improved while also the impact resistance of the material is improved. The matrix is kept austenite, the toughness of the matrix structure is improved, and the impact resistance is enhanced.
[0007] To achieve the above object, the present invention is implemented through the following technical solutions:
[0008] A medium stress abrasive wear resistant plasma cladding flux-cored welding wire, comprising an outer sheath and a flux core;
[0009] The core is composed of the following raw materials in weight percentage: 3% to 6% graphite powder, 2% to 6% high carbon ferrochrome powder, 10% to 30% chromium carbide powder, 3% to 6% ferromolybdenum powder, 45% to 65% ferrovanadium powder, 1% to 2% silicon carbide powder, 1% to 3% electrolytic manganese powder, and the balance is reduced iron powder; the outer skin is a low carbon cold-rolled steel strip.
[0010] The diameter of the flux-cored welding wire is 1.2-2.8 mm.
[0011] The particle size of the raw material is less than 380um.
[0012] The carbon content in the graphite is more than 99.0%;
[0013] The Cr content in high carbon ferrochrome powder is 65.0% to 69.0%, and the C content is 8.0% to 9.0%; the Cr content in chromium carbide is 88.0% to 92.0%, and the C content is 9.0% to 11.0%; the Mo content in ferromolybdenum powder is 57.0% to 62.0%; the V content in ferrovanadium powder is 45.0% to 53.0%; the SiC content in silicon carbide powder is greater than 96.0%; and the Mn content in electrolytic manganese powder is more than 99.9%.
[0014] A method for preparing a medium stress abrasive wear resistant plasma surfacing flux-cored welding wire comprises the following steps:
[0015] 1) Mixing the core materials according to the ratio, heating and drying in a vacuum heating furnace, and mixing them evenly in a powder mixer to obtain mixed core powder;
[0016] 2) rolling a low-carbon cold-rolled steel strip into a U-shaped groove, and then adding a mixed flux core powder accounting for 36% to 50% of the total weight of the flux-cored welding wire into the U-shaped groove; closing the U-shaped groove to wrap the flux core therein, and finally obtaining a flux-cored welding wire with a diameter of 1.2 to 2.8 mm by drawing and reducing the diameter step by step.
[0017] The drying temperature is 200-250° C. and the drying time is 90-180 minutes.
[0018] The mixing time in the powder mixer is 30 to 60 minutes.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The medium stress abrasive wear resistant plasma surfacing flux-cored welding wire prepared by the present invention has various alloy elements such as Cr and V added to the flux core. Under the high temperature of plasma surfacing, the precipitated carbon element forms various carbides with other alloy elements, generating network-distributed M7C3 type carbides and dispersed fine VC carbides, which not only has the effect of dispersion strengthening, but also can achieve fine grain strengthening, thereby ensuring the impact resistance and further improving the wear resistance of the metal coating.
[0021] 2. The outer skin of the flux-cored welding wire is a low-carbon steel strip, which is coated with a flux core. In order to achieve the composition of the final metal coating, flux cores and welding skins with different compositions are used, so that the final prepared coating can meet the design requirements. The flux-cored welding wire can adjust the powder ratio according to the working conditions to achieve rapid adjustment of the performance of the plasma surfacing metal coating, which meets the needs of the rapid development of modern industry. At the same time, the composition of the flux core can be adjusted, making the welding wire suitable for plasma surfacing process.
[0022] 3. At present, the plasma surfacing on the market is mainly powder surfacing, and the spherical powder has high cost and low powder utilization rate. There are few products using flux-cored wire as plasma surfacing material. The powder wrapped in the outer skin of the flux-cored wire of the present invention is irregular powder ground by machinery, which is economical and practical, and the utilization rate of flux-cored wire surfacing material is much higher than that of powder surfacing. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a SEM morphology of the metal coating after plasma surfacing of the flux-cored wire in Example 1.
[0024] Figure 2 This is a SEM morphology of the metal coating after plasma surfacing of the flux-cored wire in Example 2.
[0025] Figure 3 This is a SEM morphology of the metal coating after plasma surfacing of the flux-cored wire in Example 3. DETAILED DESCRIPTION
[0026] The present invention is described in detail below in conjunction with the accompanying drawings, but it should be noted that the implementation of the present invention is not limited to the following embodiments.
[0027] A medium-stress abrasive wear-resistant plasma cladding flux-cored welding wire comprises an outer sheath and a flux core.
[0028] The flux core is composed of the following raw materials in weight percentage: 3% to 6% graphite powder, 2% to 6% high carbon ferrochrome powder, 10% to 30% chromium carbide powder, 3% to 6% ferromolybdenum powder, 45% to 65% ferrovanadium powder, 1% to 2% silicon carbide powder, 1% to 3% electrolytic manganese powder, and the balance is reduced iron powder. The particle size of the above raw materials is less than 380um. The outer skin is low carbon cold rolled steel strip. The diameter of the flux cored welding wire is 1.2 to 2.8mm.
[0029] Among them, the C content in graphite is more than 99.0%; the Cr content in high carbon ferrochrome powder is 65.0%-69.0%, and the C content is 8.0%-9.0%; the Cr content in chromium carbide is 88.0%-92.0%, and the C content is 9.0-11.0%; the Mo content in ferromolybdenum powder is 57.0-62.0%; the V content in ferrovanadium powder is 45.0-53.0%; the SiC content in silicon carbide powder is greater than 96.0%; and the Mn content in electrolytic manganese powder is more than 99.9%.
[0030] When the carbon content is constant, changing the addition amount of Cr and V can change the carbides (MC, M7C3, M 23 C6) type and quantity. Using Jmatpro to calculate the type and content of the precipitated phase in the cladding layer, taking C = 4.4wt%, V + Cr = 28wt% as an example, as V increases from 11wt% to 18wt%, the MC content continues to increase, and the M7C3 content continues to decrease. When the V content increases to 15.4wt%, M 23 C6 carbide, and as the V content increases, M 23 C6 carbides are increasing. According to the characteristics of carbides, MC carbides are more conducive to improving both wear resistance and impact resistance, M7C3 carbides are more conducive to improving wear resistance, and M 23 C6 carbide is prone to cracking and flaking during impact wear, so M 23 Therefore, the flux-cored welding wire controls the mass percentage of MC:M7C3 to 1:(0.7~1.4) and avoids the formation of C6 carbides. 23 C6 is produced, making it suitable for impact energy of 2 to 4 J / cm 2 At the same time, the matrix is austenite or ferrite, the matrix structure has good toughness and strong impact resistance.
[0031] A method for preparing a medium stress abrasive wear resistant plasma surfacing flux-cored welding wire comprises the following steps:
[0032] 1) Mix the core materials according to the proportion, and then heat and dry them in a vacuum heating furnace at a temperature of 200 to 250° C. for 90 to 180 minutes. After the core powder is cooled to room temperature, mix it in a powder mixer for 30 to 60 minutes until it is uniform, to obtain a mixed core powder;
[0033] 2) rolling a low-carbon cold-rolled steel strip into a U-shaped groove, and then adding a mixed flux core powder accounting for 36% to 50% of the total weight of the flux-cored welding wire into the U-shaped groove; closing the U-shaped groove to wrap the flux core therein, and finally obtaining a flux-cored welding wire with a diameter of 1.2 to 2.8 mm by drawing and reducing the diameter step by step.
[0034] Preparation of strengthening layer: plasma surfacing is performed with the flux-cored welding wire, argon gas protection is adopted, the surfacing current is 155-165A, the welding gun travel speed is 100-150mm / min, and the ion gas flow rate is 1.5-2L / min.
[0035] Example 1
[0036] Medium stress abrasive wear resistant plasma cladding flux-cored welding wire, including sheath and flux core:
[0037] 1) Core ingredients: 19.6g ferromolybdenum, 247.4g ferrovanadium, 25.2g high carbon ferrochrome, 124.8g chromium carbide, 12.1g electrolytic manganese powder, 19.0g graphite, 4.8g silicon carbide powder, and the rest is iron powder, a total of 480g.
[0038] The flux core formula of Example 1 was used, and H08A steel strip was used for wrapping. The filling rate of the flux core was controlled at 48%, and a flux cored welding wire with a diameter of 2.4 mm was prepared by drawing. The flux cored welding wire was used for plasma surfacing, and the hardness of the obtained metal coating was 58.7 HRC, and the microstructure morphology was shown in FIG. Figure 1 .
[0039] The impact wear test was conducted using an MLD-10 impact wear tester. The impact load was 3J, the lower sample was 45 steel, the hammer mass was 10kg, the upper sample impact times were 200 times / min, the lower sample speed was 200r / min; the abrasive particle size was 1.50-2.36mm refined quartz sand (HV1235), the abrasive flow rate was 40kg / h; the impact time was 3h. The impact wear weight loss of the cladding layer was 0.2849g. Under the same conditions, the ZGMn13 high manganese steel, which is commonly used in impact wear environments, lost 0.6894g, the wear weight loss decreased by 58.7%, and the wear resistance was more than doubled.
[0040] The impact wear test was conducted using an MLD-10 impact wear tester. The impact load was 3J to simulate a medium stress impact wear environment. The lower sample was 45 steel, the hammer mass was 10kg, the upper sample impact times were 200 times / min, and the lower sample speed was 200r / min; the abrasive particle size was 1.50-2.36mm refined quartz sand (HV1235), the abrasive flow rate was 40kg / h; the impact time was 3h. The impact wear weight loss of the cladding layer was 0.2849g. Under the same conditions, the ZGMn13 high manganese steel, which is commonly used in impact wear environments, lost 0.6894g, the wear weight loss decreased by 58.7%, and the wear resistance was more than doubled.
[0041] Example 2
[0042] Medium stress abrasive wear resistant plasma cladding flux-cored welding wire, including sheath and flux core:
[0043] The core composition is: 21.4g of ferromolybdenum, 274.8g of ferrovanadium, 27.2g of high carbon ferrochrome, 126.8g of chromium carbide, 10.1g of electrolytic manganese powder, 23.3g of graphite, 5.6g of silicon carbide powder, and the rest is iron powder, totaling 500g.
[0044] The flux core formula of Example 2 was used, and H08A steel strip was used for wrapping. The filling rate of the flux core was controlled at 50%, and a flux cored welding wire with a diameter of 2.8 mm was prepared by drawing. The flux cored welding wire was used for plasma surfacing, and the hardness of the obtained metal coating was 61.8 HRC, and the microstructure morphology was shown in FIG. Figure 2 .
[0045] Example 3
[0046] Medium stress abrasive wear resistant plasma cladding flux-cored welding wire, including sheath and flux core:
[0047] The core composition is: 17.6g of ferromolybdenum, 213.6g of ferrovanadium, 19.1g of high carbon ferrochrome, 134.8g of chromium carbide, 9.4g of electrolytic manganese powder, 21.5g of graphite, 5.0g of silicon carbide powder, and the rest is iron powder, totaling 460g.
[0048] The flux core formula of Example 3 was used, and H08A steel strip was used for wrapping. The filling rate of the flux core was controlled at 46%, and a flux core welding wire with a diameter of 2.4 mm was prepared by drawing. The flux core welding wire was used for plasma surfacing, and the hardness of the obtained metal coating was 60.7 HRC, and the microstructure morphology was shown in FIG. Figure 3 .
[0049] Example 4
[0050] Medium stress abrasive wear resistant plasma cladding flux-cored welding wire, including sheath and flux core:
[0051] The core composition is: 21.6g of ferromolybdenum, 240.0g of ferrovanadium, 20.5g of high carbon ferrochrome, 138.0g of chromium carbide, 6.0g of electrolytic manganese powder, 16.0g of graphite, 5.0g of silicon carbide powder, and the rest is iron powder, totaling 460g.
[0052] The flux core formula of Example 4 was used, and H08A steel strip was used for wrapping. The filling rate of the flux core was controlled at 46%, and a flux cored welding wire with a diameter of 2.4 mm was prepared by drawing. The flux cored welding wire was used for plasma surfacing, and the hardness of the obtained metal coating was 59.0 HRC.
[0053] Example 5
[0054] Medium stress abrasive wear resistant plasma cladding flux-cored welding wire, including sheath and flux core:
[0055] The core composition is: 22.0g of ferromolybdenum, 275.0g of ferrovanadium, 14.0g of high carbon ferrochrome, 134.5g of chromium carbide, 12.0g of electrolytic manganese powder, 15.5g of graphite, 5.5g of silicon carbide powder, and the rest is iron powder, totaling 490g.
[0056] The flux core formula of Example 5 was used, and H08A steel strip was used for wrapping. The filling rate of the flux core was controlled at 49%, and a flux cored welding wire with a diameter of 2.8 mm was prepared by drawing. The flux cored welding wire was used for plasma surfacing, and the hardness of the obtained metal coating was 57.4 HRC.
[0057] Example 6
[0058] Medium stress abrasive wear resistant plasma cladding flux-cored welding wire, including sheath and flux core:
[0059] The core composition is: 15.0g of ferromolybdenum, 218.0g of ferrovanadium, 24.0g of high carbon ferrochrome, 143.0g of chromium carbide, 8.0g of electrolytic manganese powder, 21.5g of graphite, 5.5g of silicon carbide powder, and the rest is iron powder, totaling 490g.
[0060] The flux core formula of Example 6 was used, and H08A steel strip was used for wrapping. The filling rate of the flux core was controlled at 49%, and a flux cored welding wire with a diameter of 2.8 mm was prepared by drawing. The flux cored welding wire was used for plasma surfacing, and the hardness of the obtained metal coating was 63.4 HRC.
[0061]
[0062] The medium-stress abrasive wear resistant plasma surfacing flux-cored welding wire prepared by the present invention has various alloy elements such as Cr and V added to the flux core. Under the high temperature of plasma surfacing, the precipitated carbon element forms various carbides with other alloy elements, generating network-distributed M7C3 carbides and dispersed fine VC carbides, which not only has the effect of dispersion strengthening, but also can achieve fine grain strengthening, thereby ensuring impact resistance and further improving the wear resistance of the metal coating.
Claims
1. A medium stress abrasive wear resistant plasma surfacing flux-cored welding wire, characterized in that: including a sheath and a core; The core is composed of the following raw materials in weight percentage: 3% to 6% graphite powder, 2% to 6% high carbon ferrochrome powder, 10% to 30% chromium carbide powder, 3% to 6% ferromolybdenum powder, 45% to 65% ferrovanadium powder, 1% to 2% silicon carbide powder, 1% to 3% electrolytic manganese powder, and the balance is reduced iron powder; the outer skin is a low carbon cold-rolled steel strip.
2. The medium stress abrasive wear resistant plasma cladding flux-cored welding wire according to claim 1, characterized in that: The diameter of the flux-cored welding wire is 1.2-2.8 mm.
3. The medium stress abrasive wear resistant plasma cladding flux-cored welding wire according to claim 1, characterized in that: The particle size of the raw material is less than 380um.
4. The medium stress abrasive wear resistant plasma cladding flux-cored welding wire according to claim 1, characterized in that: The carbon content in the graphite is more than 99.0%; The Cr content in high carbon ferrochrome powder is 65.0% to 69.0%, and the C content is 8.0% to 9.0%; the Cr content in chromium carbide is 88.0% to 92.0%, and the C content is 9.0% to 11.0%; the Mo content in ferromolybdenum powder is 57.0% to 62.0%; the V content in ferrovanadium powder is 45.0% to 53.0%; the SiC content in silicon carbide powder is greater than 96.0%; and the Mn content in electrolytic manganese powder is more than 99.9%.
5. A method for preparing a medium stress abrasive wear resistant plasma cladding flux-cored welding wire according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Mixing the core materials according to the ratio, heating and drying in a vacuum heating furnace, and mixing them evenly in a powder mixer to obtain mixed core powder; 2) rolling a low-carbon cold-rolled steel strip into a U-shaped groove, and then adding a mixed flux core powder accounting for 36% to 50% of the total weight of the flux-cored welding wire into the U-shaped groove; closing the U-shaped groove to wrap the flux core therein, and finally obtaining a flux-cored welding wire with a diameter of 1.2 to 2.8 mm by drawing and reducing the diameter step by step.
6. The method for preparing a medium stress abrasive wear resistant plasma cladding flux-cored welding wire according to claim 5, characterized in that: The drying temperature is 200-250° C. and the drying time is 90-180 minutes.
7. The method for preparing a medium stress abrasive wear resistant plasma cladding flux-cored welding wire according to claim 5, characterized in that: The mixing time in the powder mixer is 30 to 60 minutes.
Citation Information
Cited By
Wear-resistant flux-cored wire for welding high-manganese steel lining plate and surfacing method
CN121848016A
